Dual Choice for Dual Target Anti-HIV Therapy - Marchand, Christophe (Journal of Clinical Research In HIV AIDS And Prevention, 2012)
This editorial discusses combination strategies that concurrently target viral replication and host factors in HIV therapy. It surveys candidate mechanisms, potential benefits, and safety considerations, advocating rigorous trials to balance efficacy with tolerability in diverse patient populations.